Effect of Learning Intervention on the Improvement of Students' Questioning Skills in Physics Learning - Andrian; Evendi; Saminan; Hamid, Abdul; Susanna; Ngadimin; Saputri, Mawarni; Cooper, Katelyn M; Nguyen, Tuan Dinh (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to reveal the effect of a learning intervention on the questioning ability in physics learning of the students of SMA Negeri 1 Kuta Baro. Employing a quantitative approach with a nonequivalent control group quasi-experimental design, the research involved 84 students, comprising 41 students in the experimental group (Classes X-1 and XI-1) and 43 students in the control group (Classes X-2 and XI-2). The learning intervention in the experimental class integrated the problem-based learning (PBL) model, teacher-student question-and-answer interactions, collaborative group discussions, and inter-group Q&A sessions. The research results showed that the learning intervention significantly and substantially enhanced students' questioning ability, as measured by the dimensions of questioning skills, including clarity, focus, conciseness, depth of information, and cognitive level. There was a 27.56% increase in the quantity of written questions in the experimental class, far exceeding the 7.9% increase in the control class. Although the quantity of oral questions increased in the experimental class, the cognitive level of oral questions in both groups remained low; however, their effectiveness (clarity and focus) was categorized as high. Overall, the learning intervention proved effective in facilitating the development of students' questioning skills, although further strategies were still needed to encourage questions at higher cognitive levels. Further follow-up is required to enhance students' oral questioning ability at the mental level by improving their prior knowledge of the subject matter and critical thinking skills